Influence of the polymer matrix type on cavitation resistance of composites - Dojčinović, M.; Pavlović, M.; Jezdimirović, S.; Purić, B.; A. , A. (Advanced Technologies and Materials, 2021)
Cavitation resistance of polymer matrix / basalt powder composites was determined in this work. Two types of composites were tested: epoxy resin / basalt powder composite and polyester resin / basalt powder composite. In both cases, a basalt powder was used as reinforcement in the resin (grain size 20μm, in the amount of 15 wt%). An ultrasonic vibration method with a stationary sample was used to test the cavitation resistance of composites in laboratory conditions. The change in sample mass with test time was monitored to define cavitation rate. Scanning electron microscopy was used to monitor the morphology of composites surface damage.